Daya Tarik Pesan Kelangkaan dan Kompetisi Konsumen: Peran Gaya Hidup dalam Keputusan Pembelian Pakaian Pria di Ego Brother Kupang - Mona, Handly Bernadus Biku; Goetha, Selfiana; Fallo, Apryanus (Journal of Innovation in Management, Accounting and Business, 2024)
This study aims to analyze the influence of scarcity messages, consumer competition, and self-concept, mediated by lifestyle, on the purchasing decisions of men's clothing at Ego Brothers, Kupang City. This research uses a quantitative method with SMART PLS analysis tools and involves 114 respondents selected using the accidental sampling technique. Data was collected through a questionnaire in the form of a Google Form with a Likert scale. The results of the study show that: Scarcity messages do not significantly affect lifestyle and purchasing decisions. Consumer competition significantly influences lifestyle and purchasing decisions. Self-concept significantly affects lifestyle but not purchasing decisions. Lifestyle significantly influences purchasing decisions. Lifestyle mediates the influence of consumer competition and self-concept on purchasing decisions but does not mediate the effect of scarcity messages on purchasing decisions. This research provides new insights into the role of lifestyle as a mediator in purchasing decisions and the importance of consumer competition and self-concept in influencing lifestyle and purchasing decisions of men's clothing at Ego Brothers, Kupang City.